2015
DOI: 10.4172/0974-8369.1000256
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characterization and In Vitro Effects of Human Concentrated Growth Factor Preparation: An Innovative Approach to Tissue Regeneration

Abstract: SummaryScientific background: Platelet concentrates are nowadays widely applied in different clinical fields to improve soft tissue and bone regeneration. "Concentrated Growth Factors" (CGF) is a new generation of platelet concentrate products, which exhibits an interesting clinical and biotechnological application potential. Aim of the study:The aim of this study is to assess the biological rationale for the use of CGF, by evaluating blood cell localization, the in vitro cumulative release of seven growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 76 publications
2
63
0
1
Order By: Relevance
“…The release dynamics of growth factors should be considered before obtaining the extract. Although Borsani et al assumed that release of growth factors from CGF continue for almost 8 days (Borsani et al, ), more sophistical research showed that some of the growth factors are released during 8 hr, while the release of some others continues throughout 13 days (Dohan Ehrenfest, de Peppo, Doglioli, & Sammartino, ; Honda et al, ; Zumstein et al, ). Based on these differences, the optimum concentration of CGF could vary in studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The release dynamics of growth factors should be considered before obtaining the extract. Although Borsani et al assumed that release of growth factors from CGF continue for almost 8 days (Borsani et al, ), more sophistical research showed that some of the growth factors are released during 8 hr, while the release of some others continues throughout 13 days (Dohan Ehrenfest, de Peppo, Doglioli, & Sammartino, ; Honda et al, ; Zumstein et al, ). Based on these differences, the optimum concentration of CGF could vary in studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another agent is the test tube used for blood collection, which its material may interfere with the properties of CGF (Bonazza et al, 2016;Tsujino et al, 2019 (Borsani et al, 2015), more sophistical research showed that some of the growth factors are released during 8 hr, while the release of some others continues throughout 13 days (Dohan Ehrenfest, de Peppo, Doglioli, & Sammartino, 2009;Honda et al, 2013;Zumstein et al, 2012). Based on these differences, the optimum concentration of CGF could vary in studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the centrifugation process, three blood fractions were identified (Borsani et al, 2015;Bonazza et al, 2016): the upper platelet poor plasma layer (PPP), representing the liquid phase of plasma; the lower red blood cells layer (RBC), containing erythrocytes and the middle CGF layer, consisting into three parts: the upper white part (WP), the downer red part (RP), and the middle "buffy coat" part (BC), representing the interface between WP and RP and containing leukocytes and platelets. Exclusion criteria were a systemic disorder, smoking, infection, non-steroidal anti-inflammatory drug use, and a hemoglobin level of <11 g/dL or a platelet concentration of <150,000 mm 3 .…”
Section: Cgf Preparationmentioning
confidence: 99%
“…It functions throughout the life cycle to maintain or restore the normal form and function of cells, tissues and, in some cases, organs, appendages, and whole organisms. These concentrates are obtained from the patient's own blood and contain autologous platelets, growth factors, and cytokines involved in the key processes of tissue regeneration, including cell proliferation and differentiation, extracellular matrix synthesis, chemotaxis, and angiogenesis (Borsani et al, 2015;Fioravanti et al, 2016). Recently, the use of platelet-rich preparations such as platelet-rich plasma (PRP), platelet-rich fibrin (PRF), platelet rich in growth factors (PRGF), and concentrated growth factors (CGF) has been shown to be effective in promoting the natural processes of wound healing and tissue regeneration (Ramos-Torrecillas et al, 2014;Sermer et al, 2015;Badran et al, 2017).…”
Section: Introductionmentioning
confidence: 99%